ETNOZOOLOGI MASYARAKAT DAYAK BAKATI DI DESA SELUAS KECAMATAN SELUAS KABUPATEN BENGKAYANG - Rusmiati, .; Anwari, Sofwan; Tavita, Gusti Eva (Universitas Tanjungpura, 2018)
The Dayak Bakati tribe in Seluas village has knowledge in the use of animals that have been conducted based on experiences such as animal utilization for ritual, mystic, consumption, medication and artistic value. This knowledge should be documented given the high activity of land clearing by the community that will affect the wildlife population in the area and feared the disappearance of communityâ€™s knowledge about the utilization of the animals. This study aims to determine the types of animals that are used and the utilization of animals by the Dayak tribe community in Seluas village, Seluas sub districtBengkayang regency. The method used in this research is survey method and interview technique of taking respondents using snowball sampling. The number of respondents is 22 people. There are 41 families used by DayakBakati tribe. Species from 41 families on average have only 1 species, except for familysuidae, cervidae, trionychidae, gekkonidae, and cannidae, each of which has 2 species. Utilization varies from ritual and mystical use, consumption, treatment and artistic value. Utilization of the most as consumption needs 59%. The parts of animals used include the whole body, meat, bones, blood, skin, horns, egg fat, teeth, head, liver, shell, dirt and fur. Meat is the most widely used animal body parts as many as 38 species of animals from 45 species of animals used by villagers of Seluas village, Seluas subdistrict Bengkayang regency. Wildlife management by the community for consumption by way of cooked gravy, sautÃ©ed, roasted and fried. While on the use of animals for treatment by way of drinking, applied and eaten.Keywords: Animal, Dayak Bakati, Ethnozoology, Utilization